Contextual Teaching And Learning Assisted With School Environmental Media Affect The Science Knowledge Competency Of Grade IV Elementary School - Okayanti, Gusti Ayu Made; Semara Putra, DB.Kt.Ngr. (Universitas Pendidikan Ganesha, 2020)
The lack of passionate learning makes students' science year low, as evidenced by the average score of students in science knowledge getting grades under the Minimum Completion Criteria. This study aimed to determine the significant influence of contextual teaching and learning approach assisted by school environment media on the competence of science knowledge of grade IV elementary students. This research was classified as pseudo experimentation using a non-equivalent control group design. The population was all grade IV students, with a total of 482 students. Sampling was using cluster random sampling technique. The sample group selected was grade IVB as many as 33 students as an experimental group and as many as 31 grade IV students as a control group. Data collection tools were used in the form of IPA knowledge competency tests. Posttest data. The science knowledge competency is analyzed using a t-test with polled variance formula. The experiment group's average post-test value was 82.42, and the average post-test value of the control group was 74.90. The t-test analysis obtained tcount = 3,831 and at the level of significance 5% and df = 62 obtained ttableÂ = 2,000. Because tcountÂ > ttable then H0 is rejected (failed to accept). Related to the analysis results can be concluded contextual teaching and learning approach assisted by the school environment media significantly affects the competence of science knowledge grade IV elementary school students.